2019
DOI: 10.1111/josh.12844
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and Somatic Problems: The Role of Class Victimization Levels

Abstract: BACKGROUND:The link between peer victimization and somatic problems is well-established. What is currently understudied is under what contextual conditions victims' health might be most likely to be compromised. Studies demonstrate that victims suffer from poorer adjustment when they belong to a group in which victimization is less normative (social misfit hypothesis). We examined whether the association between individual victimization and somatic problems was stronger in classrooms with lower class victimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 60 publications
6
30
0
Order By: Relevance
“…The second contribution of the study is the replication of the healthy context paradox among non-European adolescents, specifically in the South Korean middle school context. Consistent with previous results for Dutch, Finnish, and Italian youth (i.e., Garandeau et al 2018;Gini et al 2020;Huitsing et al 2012Huitsing et al , 2019Kaufman et al 2018), victimization-related distress was heightened in classrooms with a lower level of peer victimization. Because victims in a classroom with a lower level of victimization are less likely to have peers with similar victimization experiences (e.g., Schacter and Juvonen 2018), they might be more likely to believe that the causes of their mistreatment are internal, stable, and uncontrollable (i.e., characterological self-blame; Graham and Juvonen 1998;Weiner 1986).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The second contribution of the study is the replication of the healthy context paradox among non-European adolescents, specifically in the South Korean middle school context. Consistent with previous results for Dutch, Finnish, and Italian youth (i.e., Garandeau et al 2018;Gini et al 2020;Huitsing et al 2012Huitsing et al , 2019Kaufman et al 2018), victimization-related distress was heightened in classrooms with a lower level of peer victimization. Because victims in a classroom with a lower level of victimization are less likely to have peers with similar victimization experiences (e.g., Schacter and Juvonen 2018), they might be more likely to believe that the causes of their mistreatment are internal, stable, and uncontrollable (i.e., characterological self-blame; Graham and Juvonen 1998;Weiner 1986).…”
Section: Discussionsupporting
confidence: 91%
“…That is, students who experienced bullying in classrooms or schools with a low level of peer victimization and high centralization of victimization (i.e., only a few individuals are perceived as victims) felt more depressed, on average, than their counterparts in classrooms with higher levels of victimization and lower levels of centralization (Garandeau et al 2018;Huitsing et al 2012Huitsing et al , 2019. Similarly, non-intervention studies comparing victimized students have found that those in classrooms with lower levels of victimization are more likely to report somatic problems (Gini et al 2020).…”
Section: Classroom-level Peer Victimization As a Risk Factormentioning
confidence: 99%
“…For example, among 10to 12-year-olds, victims had lower self-esteem and more depressive symptoms in classrooms with lower victimization rates (Huitsing et al 2012). In another study, victimized adolescents experienced more somatic problems in classrooms with lower victimization rates (Gini et al 2020). In a daily diary study, the impact of verbal victimization on children's negative self-views was larger in classrooms with less aggression (Morrow et al 2019).…”
mentioning
confidence: 96%
“…The fact that some victimized children do not benefit from positive changes in their environment is very concerning. However, recent findings suggest that their situation might be even more problematic: Could improved school contexts actually worsen the plight of victimized children by increasing their adjustment difficulties (Garandeau, Lee, & Salmivalli, 2018;Gini, Holt, Pozzoli, & Marino, 2019;Huitsing et al, 2018;Huitsing, Veenstra, Sainio, & Salmivalli, 2012;Sentse, Scholte, Salmivalli, & Voeten, 2007)? In this article, we aim to raise awareness of the possibility of a healthy context paradox, as it has been referred to recently (Huitsing et al, 2018;Salmivalli, 2018).…”
mentioning
confidence: 99%